Elevated Growth Temperature Modifies Drought and Shade Responses of Fagus sylvatica Seedlings by Altering Growth, Gas Exchange, Water Relations, and Xylem Function - Faustino Rubio; Ismael Aranda; Rosana López; Francisco Javier Cano (Plants)
Climate change is increasing global temperatures and imposing new constraints on tree regeneration, especially in late-successional species exposed to simultaneous drought and low-light conditions. To disentangle the effects of warming from those of atmospheric drought, we conducted a multifactorial growth chamber experiment on Fagus sylvatica seedlings, manipulating temperature (25 °C and +7.5 °C above optimum), soil moisture (well-watered vs. water-stressed), and light intensity (high vs. low), while maintaining constant vapor pressure deficit (VPD). We assessed growth, biomass allocation, leaf gas exchange, water relations, and xylem hydraulic traits. Warming significantly reduced total biomass, leaf area, and water-use efficiency, while increasing transpiration and residual conductance, especially under high light. Under combined warming and drought, seedlings exhibited impaired osmotic adjustment, reduced leaf safety margins, and diminished hydraulic performance. Unexpectedly, warming under shade promoted a resource-acquisitive growth strategy through the production of low-cost leaves. These results demonstrate that elevated temperature, even in the absence of increased VPD, can compromise drought tolerance in beech seedlings and shift their ecological strategies depending on light availability. The findings underscore the need to consider multiple, interacting stressors when evaluating tree regeneration under future climate conditions.